The International Criminal Court and the construction of International Public Order - Santos, Sofia (2015)
Envisioning an international public order means envisioning an order sustained by a legal and institutional framework that ensures effective collective action with a view to defending fundamental values of the international community and to solving common global problems, in line with the universalist vision of international law. Envisioning the construction of an international public order means considering that this framework, which embraces and promotes the respect for human rights focused particularly on human dignity, is consolidating and evolving based on the International Criminal Court (ICC). The establishment of the ICC added an international punitive perennial facet to international humanitarian law and international human rights law and linked justice to peace, to security and to the well-being of the world, reaffirming the principles and objectives of the Charter of the United Nations (UN). Nevertheless, the affirmation process of an international criminal justice by punishing those responsible for the most serious crimes of concern to the international community as a whole, faces numerous obstacles of political and normative character. This article identifies the central merits of the Rome Statute and ICC’s practice and indicates its limitations caused by underlying legal-political tensions and interpretive questions relating to the crime of aggression and crimes against humanity. Finally, the article argues for the indispensability of rethinking the jurisdiction of the ICC, defending the categorization of terrorism as an international crime, and of articulating its mission with the "responsibility to protect", which may contribute to the consolidation of the ICC and of international criminal law and reinforce its role in the construction of an effective international public order.